Determination of Adopter Categories by Using Innovation Diffusion Models - Mahajan, Vijay (Institutional Knowledge at Singapore Management University, 1990)
Using the analytical logic underlying the classical adopter categorization approach proposed by Rogers, the authors suggest that adopter categories for a product innovation can also be developed by using their well-established diffusion models such as the Bass model. With data on 11 consumer durable products, they compare adopter categories generated by the classical approach and the Bass diffusion model, respectively. An application examining the diffusion of personal computers is documented to illustrate the usefulness of the adopter categorization based on the Bass diffusion model in studying differences among adopter categories.